Artificial Intelligence for Human Life: A Critical Opinion from Medical Bioethics Perspective – Part I - Khairatun Hisan, Urfa; Miftahul Amri, Muhammad (Journal of Public Health Sciences, 2022)
Since the end of the second artificial intelligence (AI) winter in 1993, AI popularity has been skyrocketing. Catalyzed by the rapid advancements of supporting technologies such as computational power and storage capacity, AI has been widely developed for various sectors of human lives. Although there is a common global consensus stating that the development of AI should consider ethical principles, until when this paper was written, the debates on how we can define an AI as ‘ethical’, how the AI ethical guidelines should be formulated, who has the rights to determine the ethical aspects of AI, and how can we reinforce the guidelines to the AI developer/operator is still going on. In this article, we summarized the research and studies related to AI development from the ethical perspective that have been conducted within the last 10 years. We discussed several cases of AI development misconduct and ‘unethical’ AI, such as biased algorithms and privacy breaches during data gathering.